Effects of Management Reporting on the Financial Performance of Manufacturing Companies in Thika - Mueni, Fidelis Moses (University of Embu, 2019)
The study was aimed at examining the effect of management reporting on the financial performance of manufacturing companies (MCs) in Thika. The specific objectives are to determine the effects of budgeting, costing system and strategic analysis (the independent variables) on the financial performance of manufacturing companies in Thika. This study discussed contingency theory which states that implementation and use of management reporting technique depends on contingent factors like environment, technology, size and structure of strategy, strategic mission and national culture, and new institutional sociology theory which states that institutionalized organizations tend to adopt structures and procedures that are valued in their social and cultural envirorunent. The target population for this study was 5 manufacturing companies where a sample size of 5 manufacturing companies was selected using convenience sampling method. The study collected primary data using questionnaire where the data was both qualitative and quantitative. The data was analyzed using Statistical Package for Social Sciences (SPSS), allowing the researcher to present information in form of tables and figures.